2005
DOI: 10.2118/05-10-05
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical Factors Affecting Geological Storage of CO2 in Depleted Oil and Gas Reservoirs

Abstract: A key to the success of long-term storage of CO2 in depleted oil or gas reservoirs is the hydraulic integrity of both the geological formations that bound it, and the wellbores that penetrate it. This paper provides a review of the geomechanical factors affecting the hydraulic integrity of the bounding seals for a depleted oil or gas reservoir slated for use as a CO2 injection zone. Potential leakage mechanisms reviewed include fault reactivation, induced shear failure of the caprock, out-of-zone hydraulic fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(64 citation statements)
references
References 0 publications
1
62
0
1
Order By: Relevance
“…In an analytical shear failure analysis, the horizontal poroelastic stressing may be estimated for the idealized case of a thin, laterally extensive reservoir (i.e., the so-called passive basin) according to [19]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analytical shear failure analysis, the horizontal poroelastic stressing may be estimated for the idealized case of a thin, laterally extensive reservoir (i.e., the so-called passive basin) according to [19]:…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, analytical techniques are indeed very useful for first-order estimates of the maximum sustainable CO 2 injection pressure, and for identification of the most critically oriented faults in the system. A first-order estimate of poroelastic stressing may be based on previous field interpretations [21,22], or by the analytical and semi-analytical approaches described above [19,20]. A coupled reservoirgeomechanical numerical modeling, on the other hand, might be suitable once more sitespecific data on geometry and material properties are available.…”
mentioning
confidence: 99%
“…Several authors (Streit and Hillis, 2004;Hawkes et al, 2005;Rutqvist et al, 2007 andVidal-Gilbert et al, 2008) have shown that the CO 2 -injection operations lead to an increase in the pore pressure inside and around the host reservoir, which results in a general decrease of the effective stress (by convention, compressive stress is positive).…”
Section: Caprock Failure Tendency Assessmentmentioning
confidence: 99%
“…Streit and Hillis, 2004;Hawkes et al, 2005). The aquifer layer can be modelled by an idealized thin and laterally extensive reservoir.…”
Section: Analytical Approach N°2mentioning
confidence: 99%
See 1 more Smart Citation